Why you cannot fit a round peg in a square hole: Path dependence of radio spectrum policy on digital dividend in Italy and the United Kingdom - Maria Massaro; Erik Bohlin (International Telecommunications Society (ITS), 2014)
The advent of digital television has triggered a revolution in the use of radio spectrum worldwide and in particular in Europe, where the digital switchover, meaning the migration process from analogue to digital broadcasting, has led to two major consequences on spectrum use. First of all, there has been an improvement in the quality and an expansion in the range of television services, but also a significant part of the Ultra High Frequency (UHF) band has become free from traditional terrestrial broadcasting usage and released for other services. In response to the outcome of the 2007 World Radiocommunication Conference (WRC-07) to allocate the upper part of the UHF band - the 800 MHz in Europe - for mobile services, Europe committed to structuring a regional plan promoting harmonisation of spectrum use across EU member states. In 2012, the first Radio Spectrum Policy Programme (RSPP) was approved. EU member states agreed on clearing the 800 MHz band from television broadcasting services and making it available for mobile services by 1 January 2013 (European Parliament & the Council, 2012). However, some EU member states showed a high degree of sensitivity about how intrusive the RSPP could be in the policy area of radio spectrum, which is considered a core area of national sovereignty. It is suffice to think that fourteen EU member states asked the European Commission (EC) to grant policy derogations due to a variety of exceptional reasons, having missed the previously agreed deadline, and nine of them have actually been granted. Different paths towards the allocation of the digital dividend to mobile services, in terms of policy and regulatory interventions, have been traced by EU member states under the EU umbrella. Moreover, Europe is carrying out studies on future spectrum requirements, including the 694-790 MHz (700 MHz) band, which will be allocated to mobile services in Europe from 2016, according to what has been stated at the 2012 World Radiocommunication Conference (WRC-12). This band is used to be referred to with the expression 'second digital dividend'.
Keywords: 330; digital dividend; spectrum policy; path dependence; mobile service; Italy; United Kingdom